Let's not wait until a crisis for change to occur: a critical analysis of patent law in South Africa and its role in (not) fulfilling the constitutional right to health - Gotora, Ngonidzaishe (Department of Commercial Law, 2025)
The right to health is enshrined in international treaties and under section 27 of the Constitution of the Republic of South Africa. It has been established that access to affordable medicines is a fundamental element to its realisation. Research has identified patent law as a potential barrier to access. Research on how patent law creates a barrier to accessing affordable medicines has been focused on identification of the flaws within South Africa's patent regime. However, the impact of the high prices on patented medicines and what this means for the binding obligations that the right to health entails is limited. The main objective of this thesis is to determine if this impact constitutes an infringement to the constitutional right to health. The secondary objective is to analyse whether solutions suggested to improve access such as encouraging use of the TRIPS flexibilities and the implementation of the Intellectual Property Policy of the Republic of South Africa Phase I has yielded the desired result. The analysis reveals that high prices of patented medicines negatively impact the population that relies on public health systems within the country. This analysis suggests that the current patent regime has resulted in the prevalence of these high prices and as such, it stands as a barrier to the realisation of the right to health. The findings show that the suggestions to improve access are yet to be utilised. To date South Africa has not utilised compulsory licences or the ‘bolar' exception as tools to improve access. Furthermore, the implementation of the IP Policy although gradual, is lacking the urgency required for the situation at hand. This thesis draws suggestions from India and Canada that may be applied to South Africa. Additionally, the thesis extracts lessons from scholars who suggest pharmaceutical companies must embody the notions of communitarian ethic as a means of replacing a profit-centred approach with a community approach when setting prices. The thesis suggests such a communitarian ethic be applied as a solution that challenges the notion of ownership and distribution in IP law.